2019
DOI: 10.1073/pnas.1915139116
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ULK1 and Beclin1 by an α-herpesvirus Akt-like Ser/Thr kinase limits autophagy to stimulate virus replication

Abstract: Autophagy is a powerful host defense that restricts herpes simplex virus-1 (HSV-1) pathogenesis in neurons. As a countermeasure, the viral ICP34.5 polypeptide, which is exclusively encoded by HSV, antagonizes autophagy in part through binding Beclin1. However, whether autophagy is a cell-type–specific antiviral defense or broadly restricts HSV-1 reproduction in nonneuronal cells is unknown. Here, we establish that autophagy limits HSV-1 productive growth in nonneuronal cells and is repressed by the Us3 gene pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 66 publications
0
35
0
Order By: Relevance
“…Interestingly, in the non-neuronal cells, inhibition of autophagy was achieved by the phosphorylation of two autophagy regulators: ULK1 and Beclin1, which are dependent on the HSV-1 protein Us3 ser/thr kinase. The authors also showed that depleting both ULK1 and Beclin1 rescued the replication of the Us3-deficient virus strain [ 49 ]. This is significant, as Us3 also plays a role in viral manipulation of cellular apoptosis [ 50 ].…”
Section: Hsv Immune Evasion Mechanismsmentioning
confidence: 99%
“…Interestingly, in the non-neuronal cells, inhibition of autophagy was achieved by the phosphorylation of two autophagy regulators: ULK1 and Beclin1, which are dependent on the HSV-1 protein Us3 ser/thr kinase. The authors also showed that depleting both ULK1 and Beclin1 rescued the replication of the Us3-deficient virus strain [ 49 ]. This is significant, as Us3 also plays a role in viral manipulation of cellular apoptosis [ 50 ].…”
Section: Hsv Immune Evasion Mechanismsmentioning
confidence: 99%
“…It would be worth testing the hypothesis that this feedback is mitigated in severe COVID-19 by modulation of autophagy ( 81 ), and inhibition of molecules like ULK1 by SARS-CoVs ( Table 2 ), in as much they can infect activated/memory T cells expressing CD147. Indeed, HSV-1 can inhibit ULK1 to escape the autophagy process ( 82 ), and previous studies on other betacoronaviruses showed that, upon cell infection, these viruses inhibit macro-autophagy ( 83 ). For instance, the porcine hemagglutinating encephalomyelitis (PHEV) betacoronavirus inhibits the expression of the ULK1 protein ( 84 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, BECN1 promotes fusion of the autophagosome with the lysosome for content degradation [85]. Proteins of negative-sense RNA viruses and DNA viruses, including Influenza A M2, HIV nef, and HSV-1 ICP34.5, target BECN1 to inhibit either nucleation of the autophagosome or fusion of the autophagosome with the lysosome to increase viral replication [86][87][88][89]. BECN1 negatively regulates the innate immune response with CGAS by preventing excessive IFN (interferon) production while promoting autophagic degradation of intracellular pathogens such as HSV-1 (Figure 1) [90].…”
Section: Coronaviruses and Becn1mentioning
confidence: 99%